Rekontekstualisasi Madilog Tan Malaka dalam Ruang Publik Virtual: Studi Kasus Konten Youtube MALAKA : Recontextualization of Tan Malaka's Madilog in Virtual Public Space: A Case Study of MALAKA's YouTube Content - Muklis Siregar; Amroeni Drajat; Hasnah Nasution; Agung Prayogo (Jurnal Filsafat Indonesia, 2026)
This article examines the recontextualization of Tan Malaka's Madilog in fostering rational-scientific reasoning within the contemporary digital society. The YouTube channel "MALAKA" serves as a philosophical discourse space that challenges established public thinking patterns. This study aims to analyze how Madilog's ideas are mediated, reinterpreted, and debated by audiences within the virtual public sphere. Employing a netnographic approach and content analysis of videos and user comments on the MALAKA channel, this research maps the dynamics of public reception toward dialectical materialism and logic. The findings reveal a spectrum of contradictory responses: ranging from support for scientific rationality and philosophical dialogue to resistance rooted in persistent mystical beliefs. This study demonstrates that the recontextualization of Madilog on YouTube has successfully transformed philosophy into an integral part of contemporary public conversation, enhancing intellectual accessibility while simultaneously creating a tension between scientific reason and local cultural constructs in the digital realm.